2022
DOI: 10.1590/pboci.2022.020
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in Temporomandibular Disorders Patients during COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Objective: To assess the influence of the COVID-19 pandemic on levels of anxiety, stress, and orofacial pain in individuals with and without TMD. Material and Methods: In this cross-sectional study, the participants were divided into two groups (n=10, each) experimental group (EG) TMD patients and control group (CG), without TMD. The presence of TMD was confirmed using the RDC/TMD. The Beck Anxiety Scale (BAI), Perceived Stress Scale (PSS), and Oral Analog Scale were used for assessment. The Beck Anxiety Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In recent years, emotional state assessment has become even more important due to the significant stress and emotional strain experienced by a significant portion of the population as a result of coronavirus disease 2019 (COVID-19), including the death of loved ones and concern for their lives. 19 In their cross-sectional analysis of Swedish national registries, Fredricson et al demonstrated a strong association between the occurrence of mental and behavioral disorders (MBD) and TMD. Pain, the most common symptom of TMD, was strongly associated with depression, anxiety and stress-related disorders, which are modified in TMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, emotional state assessment has become even more important due to the significant stress and emotional strain experienced by a significant portion of the population as a result of coronavirus disease 2019 (COVID-19), including the death of loved ones and concern for their lives. 19 In their cross-sectional analysis of Swedish national registries, Fredricson et al demonstrated a strong association between the occurrence of mental and behavioral disorders (MBD) and TMD. Pain, the most common symptom of TMD, was strongly associated with depression, anxiety and stress-related disorders, which are modified in TMD.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of the project was to create a universal questionnaire for the initial evaluation of the psychoemotional state of TMD patients that would be available to all dentists as an alternative to numerous assessment scales, such as the Beck Anxiety Inventory (BAI), the Perceived Stress Scale (PSS), the Patient Health Questionnaire-9 (PHQ-9), the Symptom Checklist 90-Revised (SCL-90-R), the State-Trait Anxiety Inventory (STAI), and the Lazarus-Folkman Ways of Coping Questionnaire. 4,19 The questionnaire is only intended as a preliminary assessment of the psychoemotional state to guide the dentist's further management of psychotherapeutic support for TMD patients. It refers to broad emotions such as lowered mood, anxiety, introversion, current mental well-being, sudden panic attacks, and self-dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%